On repeated browsing of Scots pine saplings by moose (Alces alces). - Löyttyniemi, Kari (Silva Fennica, 1985)
The size, nutrient contents and terpene composition of needles of Scots pine ( L.) saplings untouched and repeatedly browsed by the moose ( L.) were compared. Material was collected from a 14-years old and 2.5 m high pine stand in Bromarv, Southern Finland. The average length and fresh and dry weight of the needles were measured, and nutrient content (N, P, K, Ca, Mg, B, Cu) was determined.Pinus sylvestrisAlces alces